Exercise training and physical activity in children: Hard interval training or low hanging fruits to ensure normal growth and maturation for the sake of lifelong physical activity? - Heinonen, I. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Physical activity but also exercise training is considered vital in children for their normal growth and maturation. Physically active lifestyle is important for health and exercise training if children have competitive aims. But how should they train, especially if children (or parents and coaches as might often be the case) want to improve their abilities in endurance sports? Answers to this question are provided by Grendstad and Hallen who studied the effects of adding high-intensity exercise training on maximal oxygen uptake in 12-year-old youth cross-country skiing athletes.1 The study lasted 8 weeks and one group of children trained on average 4.6 times per week of which two training sessions were high-intensity interval sessions. This group was compared with a group called strength and coordination group who trained 4.1 times per week and control group which consisted of 29 Norwegian children who exercised 1.8 times per week. None of these latter groups performed high-intensity training. Essentially what they report is that maximal oxygen consumption (VO2max) increased similarly in all of these groups no matter how children trained or did not train. These findings have important implications to training practices as they suggest that high-intensity training is not required in children, and it does not provide additional benefits for VO2max as compared to normal active living or other type of training which do not focus on endurance. Although it is good to train at all exercise intensities and to learn to perform also high-intensity training when young for later if success in competitions is the goal, but as it is often considered also both physically and mentally quite demanding, training mainly by other means might provide more participation and enjoyment, which eventually might also lead to better outcomes in major issues in children sports such as dropout.2, 3 The study by Grendstad and Hallen also suggests that focusing on other type of training does not either compromise the development of VO2max if the main interest is in the endurance sports. Higher intensity training is often required for further development when fitness is high but concentrating more on "low hanging fruits" such as general active lifestyle and training various (motor) skills, technique, speed, agility, jumps, strength, balance, and coordination might develop more balanced and prepared body4, 5 for development and harder training later in adolescence and adulthood. This might also better reduce sports-related problems in youth such as overuse injuries6, 7 when training is not monotonic and too intensive. This approach also creates good abilities to try and learn new sports later in life.